Pengabdian Kepada Masyarakat: Dalam Konsep Dan Implementasi - Nurdin Nurdin (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Community service carried out by tertiary institutions should be able to carry out the functions of developing, implementing and utilizing educational and research darma products. Even though until today there are still many tertiary institutions that still misinterpret community service, in fact, the people who are targeted ultimately have a wrong perception of the tertiary darma program, where people think they get assistance for free. This ultimately forms the perception that community service activities that have been carried out by PTN and PTS, tend to lead to community service activities which are carried out free of charge. The purpose of this writing is to explain theoretically how the concept of community service really is and how it is implemented in the midst of society. Based on the discussion that has been carried out, it can be concluded that tertiary education services to the community as an institutional implementation of science, technology and arts and culture through scientific methodology so as to accelerate the rate of growth in achieving national development goals. The implementation of community service carried out by tertiary institutions has the scope of service as the practice of science, technology, and art which can include the development of science, technology and art into products that can be directly utilized by the community; Application of science, technology, and art that is relevant to the needs of the community and the demands of development; Provision of expertise assistance to the community in solving development problems; Development of research results which, according to university studies, can be utilized for the benefit of society and development so that these research results can directly benefit society and development.